Infrared spectroscopy: A tool for determination of the degree of conversion in dental composites - Moraes, Luciene Gonçalves Palmeira [UNESP]; Rocha, Renata Sanches Ferreira [UNESP]; Menegazzo, Lívia Maluf [UNESP]; De Araújo, Eudes Borges [UNESP]; Yukimitu, Keizo [UNESP]; Moraes, João Carlos Silos [UNESP] (FapUNIFESP (SciELO), 2008)
Infrared spectroscopy is one of the most widely used techniques for measurement of conversion degree in dental composites. However, to obtain good quality spectra and quantitative analysis from spectral data, appropriate expertise and knowledge of the technique are mandatory. This paper presents important details to use infrared spectroscopy for determination of the conversion degree.
Keywords: Degree of conversion; Dental composites; FTIR; Infrared spectroscopy